The Analysis of Factors that Influence Female Impulse Buying During Online Transactions - Hung, Chien-Ju (2008)
Impulse buying is seen as unplanned and unintended in-store behaviour. This study examines the factors triggering female online impulse buying behaviour by conducting a quantitative online questionnaire. Basing on previous literature, five factors including environmental stimuli, promotions and advertising, product-related factors, situational factors and customer impulse buying tendencies are analysed in this research. In addition, demographic data are also collected in this research. According to the results, all factors, except for promotions and advertising, contribute to influencing female online impulse behaviour. Moreover, concerning demographic factors, it is found that online shopping experiences and time surfing on the Internet have a positive impact on female online impulse buying behaviour.